Synthesis, Crystal Structure, DFT, TD-DFT and DOS Analysis of Bis-[2-(3-hydroxy-4-methoxyphenyl)-4,5-diphenyl-1H-imidazol-3-ium]oxalate Ethanol Solvate - Solo, Peter; Doss, M. Arockia; Pillay, Michael; Raja, Tharsius Raja William (Asian Journal of Chemistry, 2025)
A novel imidazolium-oxalate co-crystal was synthesized and characterized using spectroscopic method and single-crystal X-ray diffraction studies. The compound crystallizes into triclinic space group (P–1) with a = 8.792(3), b = 10.814(4), c = 13.024(5), α = 82.881(9), β = 75.347(9), γ = 67.811(9), a volume of V = 1108.7(7) Å3 and Z = 1. The X-ray diffraction studies confirms deprotonation of both the protons from oxalic acid and the protonation of pyrimidine-type nitrogen of the imidazole ring. The crystal structure is largely stabilized by the existence of N–H···O and O–H···O polar interactions between the protonated imidazole compounds and the oxalate ions. Density functional theory (DFT) calculations demonstrated a strong correlation between the optimized constrained structure and the experimental findings. UV-visible spectroscopy, time dependent-DFT and density of states (DOS) studies were performed to study the optical and electronic properties of the studied crystal. With a band gap of 1.807 eV, the organic crystal can be investigated for its applications in organic semiconductors and optical materials.